Socioeconomic status, parenting stress and parenting practices during the covid-19 lockdown in Serbia - Rajić, Milana M; Videnović, Marina; Krstić, Ksenija (Psihološka istraživanja, 2023)
The lockdown in Serbia imposed major challenges for parents to take on a 24/7 shift in caretaking, educating, and entertaining their children, while managing to complete the demands of their professional roles and everyday household functioning, along with the constant fear of the virus spreading and potential job loss. This study examines parenting practices (enriching activities, harsh parenting, daily structure, screen time and perception of the increase in screen time) during the COVID-19 lockdown in relation to the perceived parenting stress, parents’ socioeconomic status and their working conditions (i.e., without work obligation, working online, working from the workplace). The sample consisted of 1510 mothers of preschool children. Four socioeconomic clusters were identified using the relevant variables (education level, economic status and impact of the pandemic on the financial situation). The results showed that highly educated mothers who worked remotely during the lockdown experienced significantly higher stress of balancing working and parenting than other parents. Mothers who did not work during the pandemic spent more time in enriching activities (p
Keywords: covid 19; parenting practices; parenting stress; early childhood development